Analysis of Nurse's Clinical Education Performance based on Work Theory and The Indicator of Competence - Srinalesti Mahanani; Yulis Setiya Dewi; Widji Soeratri (Universitas Airlangga, 2014)
Introduction: Clinical Learning is a process of transformation of the student to become a professional nurse. Clinical Nurse Educator contributes to improve the quality of clinical learning because of variety of roles ranging from planning, implementing and evaluating learning clinical practice. Improving the quality of clinical practice learning, can be reached by improving the performance of Clinical Nurse Educator. The aim of this study was to know the effect of psychological variables and organizational variables to the competence and performance of Clinical Nurse Educators. Sample was Clinical Nurse Educators who work inpatient wards at Kediri Baptist Hospital inpatient wards.Method: This study was conducted in two stages. Phase I measure the competence and performance of Clinical Nurse Educator by Supervisor and students, as well as psychological variables and organizational variables by using questionnaires. Phase II was done by Focused Group Discussion to discuss about the variables that affect Clinical Nurse Educator performance. Data processed using Partial Least Square with α = 0.05, path coefficient = 0.5 and t table = 1.96.Result: The results of this research is showed that Performance Nurse Educator can be improved by increasing Individual Competence with path coefficient= 0.600 and t = 6.741. The individual competence will be increase by improving pscychological aspect nurse educator such as perception, personal aspect, motivation, learning skill and attitude with path coefficient = 0.518 and t = 2.715. Psycological Aspect can be increasing by improving Organization Variable such as Organization Resource, Salary, Organization Structure and Job Description with path coefficient = 0.825 and t = 19.658.Discussion: The conclusion of this result that increase of nurse educator competence and performance can be effort by improving psycological aspect and organizational variable